2002
DOI: 10.1074/jbc.c200578200
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation of p53 Inhibits Its Ubiquitination by Mdm2

Abstract: In response to DNA damage, the activity of the p53 tumor suppressor is modulated by protein stabilization and post-translational modifications including acetylation. Interestingly, both acetylation and ubiquitination can modify the same lysine residues at the C terminus of p53, implicating a role of acetylation in the regulation of p53 stability. However, the direct effect of acetylation on Mdm2-mediated ubiquitination of p53 is still lacking because of technical difficulties. Here, we have developed a method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
405
3
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 443 publications
(423 citation statements)
references
References 34 publications
12
405
3
3
Order By: Relevance
“…Furthermore, post-translational modifications such as acetylation may have a crucial role in the stabilization of p53 [43]. For example, acetylation may regulate the stability of p53 by inhibiting MDM2-induced ubiquitination [44]. Here, we found that depletion of hSSB1 reduced the acetylation of p53 at lysine 382 and increased the ubiquitination of p53 ( Figure 4B, 4C and 3B), indicating that hSSB1 might regulate MDM2-mediated ubiquitination by affecting the acetylation of p53.…”
Section: Discussionsupporting
confidence: 51%
“…Furthermore, post-translational modifications such as acetylation may have a crucial role in the stabilization of p53 [43]. For example, acetylation may regulate the stability of p53 by inhibiting MDM2-induced ubiquitination [44]. Here, we found that depletion of hSSB1 reduced the acetylation of p53 at lysine 382 and increased the ubiquitination of p53 ( Figure 4B, 4C and 3B), indicating that hSSB1 might regulate MDM2-mediated ubiquitination by affecting the acetylation of p53.…”
Section: Discussionsupporting
confidence: 51%
“…Acetylation stabilizes p53 by inhibiting ubiquitination and degradation. 21 Based on these data, we investigated whether resveratrol induction of Egr-1 potentially acts through SIRT1 activation. We employed a small molecule inhibitor of SIRT1, Ex-527, which consists of a racemic mixture of Ex-243, the active optical isomer and Ex-242, the inactive optical isomer, which serves as a control compound.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the same lysine residues are acetylated by histone acetyl transferases (HATs) which result in p53 stabilization and activation. [43][44][45] Finally, there are data that neddylation, 44 methylation, 46 and sumoylation (reviewed in Muller et al 47 ) of the CTD can regulate p53 functions.…”
Section: The P53 C-terminal Dna-binding Domainmentioning
confidence: 99%